High-Density μLED-Based Optical Cochlear Implant With Improved Thermomechanical Behavior - Klein, Eric; Gossler, Christian; Paul, Oliver; Ruther, Patrick (Frontiers in Neuroscience, 2018)
This study reports the realization of an optical cochlear implant (oCI) with optimized thermomechanical properties for optogenetic experiments. The oCI probe comprises 144 miniaturized light-emitting diodes (µLEDs) distributed along a bendable, 1.5-cm-long, 350-µm-wide and 26-µm-thick probe shaft, individually controlled via a n×p matrix interconnection. In contrast to our earlier approach based on polyimide (PI) and epoxy resin with different thermal expansion coefficients, the µLEDs and interconnecting wires are now embedded into a triple-layer stack of a single, biocompatible and highly transparent epoxy material. The new material combination results in a pronounced reduction of thermomechanical bending in comparison with the material pair of the earlier approach. We developed a spin-coating process enabling epoxy resin layers down to 5 µm at thickness variations of less than 7 % across the entire carrier wafer. We observed that the cross-linking of epoxy resin layers strongly depends on the spin-coating parameters which were found to be correlated to a potential separation of epoxy resin components of different densities. Furthermore, various metallization layers and corresponding adhesion promoting layers were investigated. We identified the combination of silicon carbide with a titanium-based metallization to provide the highest peeling strength, achieving an adhesion to epoxy improved by a factor of two. In order to obtain a high process yield, we established a stress-free implant release using the electrochemical dissolution of a sacrificial aluminum layer. The direct comparison of oCI probe variants using a single epoxy material and the combination of PI and epoxy resin revealed that the epoxy-resin-only probe shows minimal thermomechanical probe bending with a negligible hysteresis. The thermal probe characterization demonstrated that the temperature increase is limited to 1 K at µLED DC currents of up to 10 mA depending on the stimulation duration and the medium surrounding the probe. The optical output power and peak wavelengths of the new oCI variant were extracted to be 0.82 mW and 462 nm when operating the µLEDs at 10 mA, 10 kHz and a duty cycle of 10 %. The optical power corresponds to a radiant emittance of 407 mW/mm2, sufficient for optogenetic experiments using channelrhodopsin-2.